Indoor air temperature monitoring: A method lending support to management and design tested on a wine-aging room. (April 2015) - Barbaresi, Alberto; Torreggiani, Daniele; Benni, Stefano; Tassinari, Patrizia
Abstract: Indoor air temperature monitoring is a basic activity giving useful information in many fields such as human thermal comfort, food preservation conditions and energy simulations. The collected data can help the room management and, their elaborations, can improve energy-efficient building design. The survey equipment installation in an indoor space – sensor number and positions, record frequency – is a delicate procedure depending on several conditions related to the specific room. Nevertheless specific installation procedures are nor defined or codified in the scientific literature. This study aims at the definition of a temperature survey method, both accurate and cost-effective, able to quantify and maximize precision and accuracy of the temperature monitoring in indoor spaces, through an experimental temperature test carried out on a wine-aging room of an Italian wine farm. The method allows to identify homogeneous temperature zones, the number of sensors to be installed and the proper data recording frequency, based on the specific needs of the process under study. This method is experimentally validated by means of a test carried out on a wine-aging room. Highlights: A temperature monitoring method for indoor spaces is proposed. A preliminary test and precision definition are required before the monitoring. The method allows the homogeneous temperature identification. The method assesses the sensor possible positioning and monitor frequency. An Italian wine-aging room is used as case study.